Oncogenes induce genotoxic stress by mitotic processing of unusual replication intermediates - Neelsen, Kai J; Zanini, Isabella M Y; Herrador, Raquel; Lopes, Massimo (The Journal of cell biology, 2013)
Oncogene-induced DNA replication stress activates the DNA damage response (DDR), a crucial anticancer barrier. DDR inactivation in these conditions promotes genome instability and tumor progression, but the underlying molecular mechanisms are elusive. We found that overexpression of both Cyclin E and Cdc25A rapidly slowed down replication forks and induced fork reversal, suggestive of increased topological stress. Surprisingly, these phenotypes, per se, are neither associated with chromosomal breakage nor with significant DDR activation. Oncogene-induced DNA breakage and DDR activation instead occurred upon persistent G2/M arrest or, in a checkpoint-defective context, upon premature CDK1 activation. Depletion of MUS81, a cell cycle-regulated nuclease, markedly limited chromosomal breakage and led to further accumulation of reversed forks. We propose that nucleolytic processing of unusual replication intermediates mediates oncogene-induced genotoxicity and that limiting such processing to mitosis is a central anti-tumorigenic function of the DNA damage checkpoints.